Формотворення іменника кінь у західнополіських і суміжних говірках - Зінчук, Руслана Степанівна; Zinchuk, Ruslana S. (Товариство з обмеженою відповідальністю "Видавничий дім "Гельветика", 2016)
На матеріалі західнополіських і суміжних говірок проаналізовано формотворення іменника чоловічого роду з м’яким кінцевим приголосним основи та ненаголошеним закінченням у множині. Відзначено високий ступінь варіантності відмінкових формантів. З’ясовано чинники впливу на існування діалектних відмінностей у досліджуваній формотвірній системі. Встановлено, що специфіку формотворення субстантива кінь на діалектному ґрунті визначають інтенсивні процеси інноваційного характеру, зокрема граматична аналогія та типові для говірок фонетичні закономірності. Вказано на продуктивність фонетично видозмінених давніх флексій в окремих відмінкових позиціях іменника. Розширено ареалогічну інформацію про словоформи субстантива кінь в українських говорах.

The article sheds the light on the form inflections of a masculine noun with a soft final consonant in the stem and those with unstressed ending in plural form. The analysis has been done on the materials of Western Polissyan and adjacent patois. The author emphasizes a fairy high variability of case formants. The in-depth analysis of the materials allows to elucidate the factors which caused and influenced the existence of dialectical diversities in the form inflection system of the phenomenon under consideration. It has been proved that the specific features of the noun кінь ‘horse’ form inflections on the dialectical background are caused by the innovative intensive processes in language, particularly it concerns the phenomena of grammatical analogy and typical for dialects phonetic laws. The emphasis is laid on the productivity of the phonetically modified old flexions in certain case positions of the noun. The article presents materials expanding areal information on the word forms of the noun кінь ‘horse’ in the Ukrainian patois.
Form inflections of the noun кінь ‘horse’ in Western Polissyan and adjacent patois
Keywords: говірка; формотворення; іменник; відмінок; флексія; граматична аналогія; фонетична інновація; patois; form inflections; noun; case; flexion; grammatical analogy; phonetic innovation